Assessment of Cardiac Risk Factors and Socio Demographic Feature of Rheumatoid Arthritis in Bangladesh - Mamun, Mohammad Al; Chowdhury, M A Jalil; Sultana, Fouzia; Islam, Lohani Md Tajul; Kadir, ANM Monowarul; Jamali, Mohammod Zafar Iqbal; Fatema, Nilufar (University Heart Journal, 2025)
Patient with Rheumatoid Arthritis(RA)shows an increased risk of cardiovascular diseases. This study was to find out cardiac risk factorsand socio demography related with Rheumatoid Arthritis in hospital Bangabandhu Sheikh Mujib Medical University (BSMMU)from July 2014 to December 2015. The present study, among 384 RA patients, mean age of the patients was 42.54±1.22 years whereas 32% represented from 41-50 years. Most of the patients (82.6%) were female.Regarding education more than half of the patients (57.8%) completed primary education followed by illiterate (12.5%), secondary (12.8%), highersecondary (8.9%) and graduation (8.1%). About 71.1% were housewife followed by service holder (14.6%), business (3.1%), student (2.1%) and farmer (2.1%). Mean yearly income was 133341.14±105056.94 BDT. Almost 95.1% were married. Mean age of disease onset was 35.53±10.89 years where minimum age of disease onset was 17 years and maximum was 61 years. About 29.2%, 28.4% and 24.7% patients started disease within 31-40 years, 21-30 years and 41-50 years respectively.82% patients had no extra articular manifestations. About 13%, 1.8%, 1% patients had musculoskeletal, hematological and systemic manifestations as well.77.9% patients had no co-morbidity conditions. About 10.4%, 3.1%, 1.8% and 1.3% patients had hypertension, diabetes mellitus, hypothyroidism and ischemic heart disease as well.Cardiac risk factors were found in RA such as hypertension, diabetes mellitus, hypothyroidism and ischemic heart disease respectively. University Heart Journal 2024; 20(1): 14-17